The predictors of 3-month mortality in community-acquired pneumonia (Annals of Medical Research, 2021)
Aim: The aim of the study was to compare the pneumonia severity scoring systems (PSI, CURB-65) and inflammatory markers (CRP, CAR, NLR and PLR) in predicting community-acquired pneumonia (CAP) patients’ 3-month mortality.Materials and Methods: This study included 113 patients (43 females, 70 males) diagnosed with CAP. Demographics, comorbidities, complete blood count, arterial blood gas, electrolytes, liver-renal functions and radiological findings were evaluated. PSI and CURB-65 were classified: PSI low risk (I-III, point ≤90); PSI moderate-high risk (IV-V, point 91≤); CURB-65; low risk (0-2) and high risk (3-5). All statistical calculations were performed with SPSS 23.0 for Windows.Results: The mean age of the patients was 69.08 ± 16.58 and 3-month mortality rate among the patients hospitalized on admission was 22.4% (n=24). Albumin, hemoglobin, lymphocyte, PaO2 were lower; NLR and lactate were higher in non-survivors. Albumin and lactate were higher in CURB-65 (0-2) and (3-5) groups, respectively. NLR was significantly higher in PSI group (IV-V). Red cell distribution width and lactate were lower in PSI (I-III); basophil and PaO2 were significantly lower in PSI group (IV-V). CRP (AUC 0.744), PSI classification (AUC 0.72) and PSI scoring (AUC 0.746) showed higher mortality prediction. Conclusion: Albumin, hemoglobin, lymphocyte, PaO2 were lower; NLR and lactate were higher in non-survivors. CRP and PSI score are potent predictors of 3-month mortality.
Keywords: Community-acquired pneumonia; 3-month; mortality